Real-time OCT guidance and multimodal imaging monitoring of subretinal injection induced choroidal neovascularization in rabbit eyes. (September 2019) - Li, Yanxiu; Zhang, Wei; Nguyen, Van Phuc; Rosen, Rachel; Wang, Xueding; Xia, Xiaobo; Paulus, Yannis M.
Abstract: Choroidal neovascularization (CNV) is a major cause of vision loss that consists of abnormal growth of new blood vessels from the choroidal vasculature. High resolution in vivo imaging of animal models is essential to better elucidate and conduct research on CNV. This study evaluates a novel multimodal imaging platform combining optical coherence tomography (OCT) and photoacoustic microscopy (PAM). Using real-time OCT guidance subretinal injection to induce and multimodality imaging system to monitor CNV over time in rabbit eyes. The significance of our work lies in providing the optimal setting and conditions to make use of the OCT image guided system to improve the consistency and reproducibility of experimental results in subretinal injection induced CNV model in rabbits. For the first time, this study successfully demonstrated the dual-modality PAM-OCT system, without using exogenous contrast agents, can detect and visualize CNV in the rabbit eye with high resolution. This is promising system for diagnosing and monitoring CNV. Highlights: Multimodal real-time induced and imaging CNV in rabbit eyes.